Penerapan Model Discovery Learning Berbantuan Prezi untuk Meningkatkan Pemahaman Konsep dan Kemampuan Kolaborasi Pada Materi Alat Optik - Nur Afifah Muthmainnah; Widha Sunarno; Rini Budiharti (Universitas Sebelas Maret, 2023)
The research aims to: (1) Improve the understanding of the concept of students with the prezi-aided discovery learning model (2) Increase the ability of students to collaborate with the Prezi-assisted Discovery Learning model. The research was designed using the Kemmis and Mc. Taggart models and was conducted in two cycles. Data collection techniques use test, interview, observation, and documentation/study techniques. Data analysis techniques use qualitative and quantitative analysis. Data validation techniques use instrument validation and triangulation techniques. The research resulted in the application of a prezi-aided discovery learning model on the material Optical Tools was able to improve the understanding of the concept, but has not improved the ability of collaboration of students of class XI MIPA 1 State High School 5 Surakarta teaching year 2021/2022. The percentage of knowledge proficiency increased from 31.43% with the average student score of 65.49 in the pre-cycle to 80% with an average score of 81.4 in the first cycle, and 91.43% in the second cycle with a mean score of 87,51. In terms of collaborative skills improved from pre-recycle 50% to 88,57% in the I cycle and increased in the II cycle to 100%.